Intraoperative augmented reality with heads-up displays in maxillofacial surgery: a systematic review of the literature and a classification of relevant technologies. Issue 1 (January 2019) - Bosc, R.; Fitoussi, A.; Hersant, B.; Dao, T.-H.; Meningaud, J.-P.
Abstract: Although the term augmented reality appears increasingly in published studies, the real-time, image-guided (so-called 'hands-free' and 'heads-up') surgery techniques are often confused with other virtual imaging procedures. A systematic review of the literature was conducted to classify augmented reality applications in the fields of maxillofacial surgery. Publications containing the terms 'augmented reality', 'hybrid reality', and 'surgery' were sought through a search of three medical databases, covering the years 1995–2018. Thirteen publications containing enough usable data to perform a comparative analysis of methods used and results obtained were identified. Five out of 13 described a method based on a hands-free and heads-up augmented reality approach using smart glasses or a headset combined with tracking. Most of the publications reported a minimum error of less than 1 mm between the virtual model and the patient. Augmented reality during surgery may be classified into four categories: heads-up guided surgery (type I) with tracking (Ia) or without tracking (Ib); guided surgery using a semi-transparent screen (type II); guided surgery based on the digital projection of images onto the patient (type III); and guided surgery based on the transfer of digital data to a monitor display (type IV).